Sustained AMPK Activation and Proline Metabolism Play Critical Roles in the Survival of Matrix-Deprived Transformed Cells - Saha, Manipa; Deshpande, Neha; Dubey, Abhinav; Pal, Debnath; Atreya, Hanudatta S.; Rangarajan, Annapoorni (Frontiers in Cell and Developmental Biology, 2021)
Attachment to the matrix is critical for the survival of adherent cells, whereas detachment triggers death by apoptosis. Therefore, solid tumors must acquire the ability to survive the stress of matrix-detachment to transit through circulation and seed metastases. Although a central role for energy metabolism in cancer progression is well established, what distinguishes its role in the cellular state of the matrix-deprived form compared to the matrix-attached form is not fully understood yet. Using an in vitro transformation model dependent on simian virus 40 (SV40) small t (ST) antigen for cellular survival and proliferation in matrix-deprived conditions, we demonstrate that 5'-adenosine monophosphate-activated protein kinase (AMPK) activity is elevated and sustained under matrix-deprived conditions in ST-expressing fibroblasts. Additionally, these cells display elevated energy (ATP) levels under matrix-deprived conditions in contrast to cells lacking ST expression. The elevated ATP levels are coupled to increased levels of proline in ST-expressing cells, as revealed by metabolomics studies. The AMPK-dependent upregulation of proline oxidase, an enzyme of proline degradation, is a key link for elevated ATP levels. This functional link is further established by proline supplementation concomitant with AMPK activation in matrix-deprived cells lacking ST antigen, yielding ATP and enhancing survival. Thus, our data establishes a key role for AMPK-dependent regulation of proline metabolism in mediating energy homeostasis and promoting survival of matrix-deprived cells. These findings identify key markers that distinguish the metabolic states of matrix-detached and matrix-attached transformed cells and have implications in developing novel therapeutic strategies for specifically targeting matrix-detached metastasizing cancer cells.